HISTOMORPHOCHEMICAL STUDIES ON MEDIASTINUM TESTIS OF BUFFALO FETUS - SINGH, I; BANSAL, N; UPPAL, V; GUPTA, A (The Indian Journal of Animal Reproduction, 2022)
Histomorphochemistry was conducted on the mediastinum testis of buffalo fetuses collected from a local abattoir immediately after the sacrifice of buffalo. The results revealed that mediastinum testis was comprised of rete-testis, blood and lymph vessels, differentiating fibroblasts and mesenchymal cells at 15.5 cm curved crown rump length (CVRL). At 20 cm CVRL, the rete tubules were luminated lined by simple cuboidal to columnar type of epithelium. The connective tissue surrounding the rete-testis contained abundance of collagen fibres, few nerve fibres, elastic fibres and reticular fibres. The reaction of acid and neutral mucopolysachharides, sudanophilic lipids and basic proteins were moderate to strong in the mediastinum testis. The activity of phosphatases and dehydrogenases was weak to moderate in the mediastinum testis. The presence of various histochemical and histoenzymic activites in the mediastinum may be correlated with developmental changes during early fetal life.